Prescribing Pattern of Antidiabetic Drugs amongst Pre-obese Diabetic Patients in a Tertiary Care Hospital, India - Sougata Sarkar; Vartika Srivastava; Adrija Roy; Manjushree Mohanty (Issues and Development in Health Research Vol. 6, 2021)
Background: In order to improve the prescription quality and rational prescribing pattern promotion there is an inevitable need to investigate the factors that affect doctors’ prescription patterns. Defining drug prescription and consumption pattern provides advantageous feedback to prescribers in order to improve their prescribing behaviour. Diabetes is a common non communicable disease. It leads to high morbidity and mortality due to the disease itself and its diverse complications like CAD, hypertension, renal complication, retinal damage, neurological disorders, generalised infections etc. With such multifactorial background of high prevalence, progressive nature of the disease, availability of multiple therapeutic regimens prescribed on trial and error basis, the treatment is individualised and neither complete nor satisfactory. Objectives: This study was undertaken to analyse the current prescribing pattern in pre-obese patients of type 2 diabetes mellitus with regard to drug/drugs per prescription, dose, duration of treatment and frequency of change of drugs. Methods: This is a prospective,parallel group, comparative observational study, performed in the department of pharmacology and Endocrinology in KIMS Bhubaneswar, between 2014 to 2016. The enrolled pre-obese patients were divided as a)New diabetic b)Old diabetic(<3 years duration).Each category was further divided into four subgroups according to the treatment recieved a)Monotherapy-Metforminb)Combination therapy-Metformin+another antidiabetic groups,preferably sulfonylureas, alphaglucosidase inhibitors or DPP 4 inhibitors c)Triple therapy( Metformin+SU+Voglibose or Gliptins or Glitazones) d)Insulin with other oral hypoglycemic drugs. Results: In the study of prescribing pattern, it was observed that most prescriptions in this tertiary care hospital were found to be in compliance with the ADA guidelines. Metformin monotherapy was prescribed as initial treatment. Sulphonylureas/Gliptins/Alpha glucosidase inhibitors/thiazolidinediones were used as second line therapy, in addition to metformin or as monotherapy according to patient requirement, tolerability and cost. Conclusions: The antidiabetic medications prescribed in this hospital, were found to be in compliance with ADA guidelines.